(untitled) (Colombia Medica, 2012)
Introduction: Although the association of infection by toxoplasmosis with the development of nephrotic syndrome is uncommon, cases of this association have nevertheless been reported in the literature for more than two decades, not only for congenital toxoplasmosis, but also in acquired cases, and occasionally in immunocompetent patients. Results: A case is presented of an immunocompetent patient aged 15 with clinical and laboratory indications of nephrotic/nephritic syndrome, in whom serological tests showed toxoplasma infection. Conclusion: The presentation of nephrotic syndrome in ages where it is not commonly seen, leads to clinical suspicion of secondary causes. Active search for possible causes should include common tropical infections.